Rozhodování s podporou diskriminační analýzy - Linda, Bohdan (Univerzita Pardubice, 2002)
The discrimination analysis is a multivariable statistical method with the aim to find the optimal assignment regulation and prediction, into which of k groups a watched element belongs to. Several characteristics are measured at every element. They express its features. It means, that this element is characterised by means of a random variable X=(X1, X2, ..., Xm). The final result of this procedure is a model, that allows to predict the pertinence of the watched element to the certain group on the basis of measured values (x1, x2, ...xm).
Keywords: statistické metody; diskriminační analýza; veřejná správa